The Superior Outcome of Collagen Nanosilver in Increasing Macrophage and Collagen on Deep Dermal Burn Wound Healing - Mukti, Anggun Ari; Prasetyo, Awal; Prajoko, Yan Wisnu; Najatullah, Najatullah; Susilaningsih, Neni (Open Access Macedonian Journal of Medical Sciences, 2022)
AIM: This study aims to prove the superior outcome of collagen nanosilver in increasing macrophage and collagen on deep dermal burn wound healing. METHODS: This study was a randomized control trial design. All animals used were male Sprague Dawley rats aged 12–14 weeks old and weighed about 200–250 g. Each rat gets four site injuries and is given treatments. The treatment group includes: I (negative control using NaCl 0.9%), II (positive control using silver sulfadiazine cream), III (treatment with nanosilver collagen cream 1%), and IV (treatment with collagen nanosilver cream 2%). Macrophages counts were assessed using IHC F40/80 and collagen density was assessed using Masson’s trichrome staining. RESULTS: Macrophage on day 6 showed a significant difference as seen in group III and group IV. A significant difference was also obtained between macrophage on day 3 and day 6 from group IV, likewise between collagen between day 3 and day 6 from group III and IV. Collagen nanosilver acts as an antimicrobial and anti-inflammatory agent by increasing the mechanism of activation and migration of macrophages to the site of injury. Moreover, this formula modulated the collagen deposition, which forms the tissue fibers which ultimately provide a conducive environment for wound healing. CONCLUSION: Collagen nanosilver has a superior outcome in the increasing macrophage cell count and collagen density of deep dermal burn wound healing.